IMPLEMENTASI KAJIAN HADIS TEMATIK DALAM KEHIDUPAN SOSIAL MASYARAKAT - Muhammad Fahrul Ihsan; Muhammad Alif (Adisam Publisher, 2026)
Thematic hadith research represents a crucial method for comprehensively grasping hadith by gathering different narrations linked to a specific theme. Nevertheless, the application of thematic hadith studies in social life tends to be incomplete and has not been thoroughly analyzed. This article seeks to examine how thematic hadith studies are applied in the community’s social life, focusing on their applications, ethical standards, and societal effects. This research uses a qualitative methodology, primarily relying on library research. Data were gathered from primary hadith collections and related literature via thematic searches employing pertinent keywords and were examined through classification and content analysis methods. The results suggest that thematic hadith research can be applied in societal contexts by strengthening moral values, social ethics, and communication practices based on the teachings of the Prophet Muhammad (peace be upon him). This implementation includes elements of interpersonal relationships, social cohesion, fairness, and acceptance within the community. Additionally, thematic hadith research offers explicit ethical principles for social engagement, including honesty, mutual respect, and steering clear of actions that could harm others. Consequently, thematic hadith research serves as both an academic method and a practical basis for promoting a peaceful and civilized society.